Acceptance of liver pâté with reduced content of salt and sodium - Polak, Tomaž (Array, 2018)
The aim of this study was to produce liver pâté with reduced salt content that would have acceptable sensorial and textural properties. Sodium content in pâtés was reduced by excluding phosphate mixture (0.15%) and reducing the addition of sea or nitrite curing salts from 1.0% to 1.7%. The content of protein, fat, minerals and water was determined in control liver pâté, produced with 1.4% of curing salts. In all experimental groups of pâtés chemical parameters (content of sodium by ionoselective electrode and NaCl by the Volhard method), instrumentally measured fat and water exudation of the emulsions, colour and texture parameters were determined, along with evaluation of the sensory attributes (descriptive analysis). These pâtés with different types of salt, phosphate and levels of salt significantly differed in their chemical, instrumentally measured colour and texture parameters, and in sensory attributes (colour, saltiness, aroma, texture and overall acceptability). With respect to the colour of liver pâté, it is better to use curing salts, as pâtés have a pinker colour, while pâté with sea salt has a brighter colour. It is also reasonable to use the curing salts for better aroma intensity and overall acceptability. Pâtés with phosphate are less salty, they exclude less fat and water, and are more firm than those without phosphate, but too firm texture of pâté is not desirable. In pâtés salt can be reduced to 1.2% (curing salts) or 1.0% (sea salt), and consequently Na+ content decreased for 11%-27%, depending on type of salt and addition of phosphate mixture. Pâtés with 1.5% of curing salts and pâtés with 1.3%1.5% of curing salts and phosphate most closely match (Linear discriminant analysis) the control group with the best overall acceptability (1.4% of curing salts).